Pengaruh Online Customer Review, Online Customer Rating, Dan Harga Terhadap Keputusan Pembelian Produk Azarine Melalui Marketplace Shopee (Studi Pada Mahasiswa Universitas Trunojoyo Madura) - Vira Anggita Subiyantoro; Darul Islam (Management Department of Economics and Business Of Trunojoyo Madura University, 2026)
The cosmetics and beauty sector is developing at a rapid pace. Since their product went viral on social media some time ago, Azarine's sales have increased a lot. To maintain the availability of its products, Azarine must be able to compete with other local cosmetic companies. Considering that, compared to other local products, Azarine cosmetics are still at the bottom. Finding out whether online customer reviews, online customer rating and price have a major impact on consumers ' decision to buy Azarine goods is the aim of this study. The methodology used in this study is quantitative research. A total of 119 respondents participated in this survey, which used the purposive sampling method. Partial Least Square (PLS) analysis SmartPLS version 4 is a technique used to analyze data. Based on the hypothesis test results, the decision of Trunojoyo Madura University students to buy Azarine products is significantly influenced by the price and rating online. Meanwhile, the decision of Trunojoyo Madura University students to buy Azarine goods was not significantly influenced by online Customer review variables. As a way to apply the theory learned in lectures and as a source of knowledge and reference for further research, this research is very helpful in expanding and adding to understanding.